Phytochemical Profiles and Cytotoxic Activity of Bursera fagaroides (Kunth) Engl. Leaves and Its Callus Culture - Nancy Pérez-Mejía; María Luisa Villarreal; Jessica Nayelli Sánchez-Carranza; Leticia González-Maya; Manasés González-Cortazar; Anabel Ortíz-Caltempa; Laura Alvarez (Plants, 2024)
Bursera fagaroides, popularly used in México, possesses bioactive lignans. These compounds are low in the bark, and its extraction endangers the life of the trees. The aim of the present investigation was to search for alternative sources of cytotoxic compounds in B. fagaroides prepared as leaves and in vitro callus cultures. The friable callus of B. fagaroides was established using a combination of plant growth regulators: 4 mgL−1 of 2,4-dichlorophenoxyacetic acid (2,4-D), 1 mgL−1 Naphthaleneacetic Acid (NAA) and 1 mgL−1 Zeatin. The maximum cell growth was at day 28 with a specific growth rate of μ = 0.059 days−1 and duplication time td = 11.8 days. HPLC quantification of the dichloromethane callus biomass extract showed that Scopoletin, with a concentration of 10.7 µg g−1 dry weight, was the main compound inducible as a phytoalexin by the addition of high concentrations of 2,4-D, as well as by the absence of nutrients in the culture medium. In this same extract, the compounds γ-sitosterol and stigmasterol were also identified by GC-MS analysis. Open column chromatography was used to separate and identify yatein, acetyl podophyllotoxin and 7′,8′-dehydropodophyllotoxin in the leaves of the wild plant. Cytotoxic activity on four cancer cell lines was tested, with PC-3 prostate carcinoma (IC50 of 12.6 ± 4.6 µgmL−1) being the most sensitive to the wild-type plant extract and HeLa cervical carcinoma (IC50 of 72 ± 5 µgmL−1) being the most sensitive to the callus culture extract.